Mutation analysis of β-thalassemia in East-Western Indian population: a recent molecular approach - Shah, Parth S (Appl Clin Genet, 2017)
BACKGROUND: β-Thalassemia is the most prevalent genetic disorder in India. Its traits and coinheritance vary from mild to severe conditions, resulting in thalassemia minor, intermediate, and major, depending upon many factors. PURPOSE: The objective of this study was to identify the incidence of β-thalassemia traits, their coinheritance, and mutations, as well as to support the patients already diagnosed with β-thalassemia in East-Western Indian population for better management. PATIENTS AND METHODS: Seventy-five referral cases for β-thalassemia were analyzed for various β-thalassemia traits, heterozygosity, and homozygosity conditions. Blood phenotypic parameters using cell counter and capillary electrophoresis were investigated. Analyses of eight common mutations of thalassemia in India were carried out using polymerase chain reaction-amplification refractory mutation system, end point polymerase chain reaction, and DNA sequencing methods. RESULTS: Of these (75) referral cases from East-Western Indian region, 68 were positive for β-thalassemia (90.67%). The majority of case types were of β-thalassemia minor (49, 65.33%), followed by HbE traits (6, 8.0%) and β-thalassemia major, including heterozygous and homozygous (5, 6.66%; 4, 5.33%) types and then HbE homozygous (2, 2.66%), as well as one each of the HbE/β-thalassemia and HbD/β-thalassemia (1, 1.34%) combination. Mutation analysis also revealed that the highest frequency of mutation was c.92+5G>C (41, 60.29%) followed by deletion 619bp (9, 13.23%) and c.79G>A (8, 11.76%) in our study group. Five cases (nos. 24, 27, 33, 58, and 71) exhibited coinheritance between β(0)/β(+) (2), β(0)/β D (1), and c.124_127delTTCT/β(+) or β(0)(2) affecting the Rajasthani and Gujarati populations in our study of the Western region of India. CONCLUSION: We strongly recommend these Western populations for genetic screening before adopting reproductive technologies and interracial marital relations.